Exploring effect of utilizing geometer sketchpad on performance and mathematical thinking of secondary mathematics learners. - Abu Bakar, Kamariah; Ahmad Tarmizi, Rohani; Mohd. Ayub, Ahmad Fauzi; Md. Yunus, Aida Suraya (2008)
Numerous studies have shown the positive impact of integrating technological tool in the teaching and learning process of mathematics in the classroom.The teaching and learning of geometry utilizing dynamic geometry softwares have been explicitly indicated in the Malaysian secondary school Mathematics syllabus (Kementerian Pelajaran Malaysia,2003). Teachers were recommended to utilize technological software and one such dynamic geometry softwares licensed to be used in the Malaysian schools in the Geometer's Sketchpad (GSP) software). In this study, the effects of integrating the GSP in teaching and the traditional teaching strategy were explored and compared. Specifically, the effects on mathematical performance in secondary mathematics and students’ attitudes towards the respective approaches used to teach the groups were investigated. The mean overall mathematical performance for the group using the GSP was 11.78 (SD = 4.10) meanwhile the mean overall performance for traditional teaching strategy group was 13.03 (SD = 3.65). Independent samples t-test results showed that there was no significant difference in mean mathematical performance between the GSP group and the traditional teaching strategy group, [t (90) = 1.552, p>0.05]. However, findings also indicated that the use of GSP induced higher mathematical thinking process amongst the GSP group. These findings indicated that the use of GSP had an impact on both mathematical thinking process and performance. However, these findings provided evidences of limited and deficient use of the technology, specifically in the teaching of mathematics at the Malaysian secondary level.